Mobile payments: How digital finance is transforming agriculture - Babcock, Lee H. (Technical Centre for Agricultural and Rural Cooperation, 2015)
Leading up to the 2014 Fin4Ag – Revolutionising finance for agri-value chains international conference, the Technical Centre for Agricultural and Rural Cooperation (CTA) commissioned a study to explore the state of digital/mobile payments in agriculture. CTA is pleased to present the results of the study that it believes will make an important contribution to the body of knowledge on this topic. The study was carried out using three case studies; SmartMoney from Uganda, NWK Agri-Services from Zambia and Rice Mobile Finance (RiMFin) from Ghana.